International reserves, current account imbalance and external debt : evidence from Malaysia. - Nor, Eliza; Mohamed, Azali; Law, Siong Hook (International Islamic University Malaysia, 2008)
The purpose of the study is to analyze both the short-run and long-run demand for international reserves in Malaysia for the period 1970-2004. The autoregressive distributed lag (ARDL) bounds testing approach proposed by Pesaran, Shin, and Smith (2001) is used to test for the existence of cointegration relationship between the demand for international reserves and its determinants. The empirical results suggest that current account balance and short-term external debt significantly affect the demand for international reserves both in the long run and short run.